PENGARUH FDR, BAGI HASIL, PEMBIAYAAN JUAL BELI, SEWA MENYEWA DAN NPF TERHADAP PROFITABILITAS BANK UMUM SYARIAH 2016-2020 - Hendra H. Dukalang; Moh Agus Nugroho (Politeknik Negeri Jakarta, 2022)
This study is to determine whether Financing to Deposit Ratio (FDR), Sales and Purchase Financing (PJB), Profit Sharing Financing (PBH), Leasing Financing (PSM) and Non-Performing Financing (NPF) have a positive or negative effect on profitability or Return. On Assets (ROA) at Islamic Commercial Banks in Indonesia for the 2016-2020 period. The type of research used in this research is quantitative research. The data collection used in this research is secondary data collection, which is accessed from the internet, namely on the OJK website in the form of financial reports in the form of quarterly reports, namely Islamic Commercial Banks for 2016-2020. Data analysis that will be used in this research is descriptive statistical analysis method and panel data regression analysis which is calculated using Eviews 10 computer technology and Microsoft Excel where this research analyzes Profit Sharing Financing, Sales and Purchase Financing, Rental Financing, FDR and NPF on profitability (ROA). The results of this study show that Financing to Deposit Ratio (FDR) and Leasing Financing (PSM) have a negative effect on Return On Assets (ROA). Meanwhile, Sales and Purchase Financing (PJB), Profit Sharing Financing (PBH), Non- Performing Financing (NPF) have a positive effect on Return On Assets (ROA). Keywords: Profitability, Sharia Commercial Banks